HOMOLOGY MODELING EPITOP ISOCITRATE DEHYDROGENASE TIPE 1 (R132H) MENGGUNAKAN MODELLER, I-TASSER DAN (PS)2 UNTUK VAKSIN GLIOMA - Yeni Yeni; Daryono Hadi Tjahjono (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Glioma is a type of primary malignant brain tumor. The presence of gliomas can be characterized by a mutation R132H of isocitrate dehydrogenase type 1 (IDH1). IDH1 (R132H) contains specific immunogenic epitopes to the tumor. It is appropriate to be used as a gliomas vaccine. Therefore, it was necessary to do homology modeling for IDH1 (R132H) epitopes. TMHMM, MEMSAT-SVM and MEMSAT3 were used to predict transmembrane topology of IDH1 (R132H). Analysis of IDH1 (R132H) epitopes was performed using NetMHCII and IEDB®. The antigenicity of epitopes were predicted using VaxiJen to obtained 91 epitopes. Homology modeling using Modeller, I-TASSER and (PS)2 was established for the epitopes that have probability as tumor antigen. The results of homology modeling of IDH1 (R132H) epitopes were validated by MolProbity, ProSA-web dan QMEAN. A 3D stucture model of the epitopes was selected from three models from the homology modeling based on the validation results. Refinement was established on the epitopes using GalaxyRefine and GROMACS for energy minimization.